PROBLEMS OF DETERMINING TEMPORAL LIMITS OF HUMAN LIFE: CRIMINAL LEGAL ASPECT - Lysko, Tetiana; Ustymenko, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate and comprehensively analyze some problematic issues of determining the temporal boundaries of human life in terms of criminal law by determining the origin and termination of the right to life, studying the legal regulation of deprivation of human life at his request, determining the palliative care as a possible alternative to euthanasia in Ukraine and studying of the human right to a dignified end of life in Ukraine in criminal legal aspect. Methods: general philosophical, general scientific and special legal methods, in particular formal-legal, formal-logical, historical, method of analysis, method of synthesis, etc. Results: it was found that the moment of origin of the right to human life is controversial today, because the beginning of human life de jure does not coincide with the beginning of human life de facto; it was also found that the moment of termination of life comes the end of the right to life, and the problem of saving a person’s life at his request is very relevant today. Discussion: there are three main approaches, according to which the right to life is acquired: from birth, from conception, at different times of fetal development; the moment of termination of the life is the fact of death of a person, which is confirmed by the protocol of death of the human brain; today in Ukraine there is a ban on euthanasia, there is only one way to "circumvent" euthanasia: palliative medicine through the activities of hospices. Therefore, it is necessary to recognize that social relations are dynamic and flexible, as well as changing due to scientific and technological progress. Accordingly, legislation must also be flexible in order to meet the requirements of its time. Sooner or later, Ukraine will face the issue of legalizing euthanasia, including the human right to a decent end to life, then there will be a need for clear legal regulation of these processes to avoid abuse of the so-called «right to die» for any selfish motives. And while this issue is unresolved, the right to life remains a fundamental right, as well as an inalienable and absolute right that the state has committed to protect citizens.